A Pair of "ACEs". (January 2022) - Hersh, E.V.; Wolff, M.; Moore, P.A.; Theken, K.N.; Daniell, H.
The emergence of the COVID-19 viral pandemic has generated a renewed interest in pharmacologic agents that target the renin angiotensin system (RAS). Angiotensin-converting enzyme 1 (ACE1) inhibitors decrease the synthesis of angiotensin II (Ang II) from its precursor angiotensin I and inhibit the breakdown of bradykinin, while Ang II receptor blockers antagonize the action of Ang II at the receptor level downstream. The actions of both classes of drugs lead to vasodilation, a blunting of sympathetic drive and a reduction in aldosterone release, all beneficial effects in hypertension and congestive heart failure. ACE2 cleaves the vasoconstrictor Ang II to produce the anti-inflammatory cytoprotective angiotensin 1–7 (Ang 1–7) peptide, which functions through the G protein–coupled receptor MAS to counteract the pathophysiologic effects induced by Ang II via its receptors, including vasoconstriction, inflammation, hypercoagulation, and fibrosis. SARS-CoV-2 enters human cells by binding ACE2 on the cell surface, decreases ACE2 activity, competes for ACE2 receptor-binding sites, and shifts the RAS toward an overexpression of Ang II, accounting for many of the deleterious effects of the virus. Thus, there is great interest in developing recombinant ACE2 as a therapeutic for prevention or treatment of COVID-19. Notably, ACE2 is highly expressed in the oral cavity, and saliva and dorsum of the tongue are major reservoirs of SARS-CoV-2. Cost-effective methods to debulk the virus in the oral cavity may aid in the prevention of viral spread. Here we review the pharmacology of targeted small molecule inhibitors of the RAS and discuss novel approaches to employing ACE2 as a therapeutic for COVID-19.